Evaluating Serum Biomarkers (DPP-4, GLP-1, Ki-67 Protein) Levels for Early Detection of Diabetic Breast Cancer - Hadi , Hadi Hassan; Al-Ziaydi, Ahmed Ghdhban (Medical Science Journal for Advance Research, 2024)
Background: Breast tumours are the second most common cancer in women. A mammary cancer is a multi-step process that involves several cell types and is yet difficult to prevent globally. One of the best ways to prevent breast cancers is by early detection. In many affluent nations, the 5-year proportional perseverance ratio for people with mammary neoplasms is over 80% because to early detection. Over the past ten years, significant progress has been made in both the understanding of mammary tumours and the development of preventative interventions. Diabetes, often known as diabetes mellitus (DM), is a collection of illnesses characterized by elevated blood sugar levels brought on by flaws in the body's capacity to make and/or utilize insulin. Objectives: This study aimed to evaluate the levels of serum biomarkers (DPP-4, GLP-1, Ki-67 protein) in individuals with diabetes, breast cancer, diabetic breast cancer, and a control group. Methods: The samples were taken from individuals at Al-Najaf Teaching Hospital and the Najaf Cancer Centre between 30/10/2023 and 1/3/2024. The blood samples were 120 blood samples acquired from Iraqi subjects. The participants included four groups and each group consisted of 30 participants, (Diabetes type 2 patient group, Breast cancer patient group, Diabetic breast cancer patient group, and Control group). Results: The difference in serum DPP-4 levels, between diabetic, breast cancer individuals and healthy control groups, is statistically noteworthy. The results show a higher DPP-4 level in patient groups than in the control group. While there was no significance in the GLP-1 and Ki-67 proteins in the patient and control groups. Conclusion: These results suggest that high serum DPP-4 could serve as a useful screening marker for the early detection of diabetic breast cancer. ًWhile, The lack of differences in GLP-1 and Ki-67 proteins levels across the groups indicates these biomarkers may not be as informative for identifying diabetic breast cancer in this population.